Media portrayals and social stigma surrounding COVID-19 survivors: a content analysis of Chinese media coverage - Weili Wang; Wenxuan Zhang (BMC Public Health)
Abstract Background The COVID-19 pandemic has generated widespread uncertainty, leading to an overabundance of information and fuelling public fear and confusion. Concerns regarding the transmissibility and long-term effects of the virus on survivors have exacerbated societal stigma towards those who have recovered from COVID-19. This study analyses Chinese media coverage to explore the ways in which COVID-19 survivors are portrayed and how these portrayals may contribute to the broader narrative of stigmatisation. Methods This study employs content analysis of 440 news articles from four major Chinese media outlets, spanning the period from January 2020 to March 2023. The sample includes two state-sponsored outlets, People’s Daily and Global Times, and two market-oriented outlets, Caixin Weekly and Sanlian Lifeweek. By comparing media coverage across these outlets, the research investigates how representations of COVID-19 survivors varied across different media outlets. Results Disparities in media portrayals of COVID-19 survivors were found. State-sponsored media, such as People’s Daily and Global Times, generally depicted COVID-19 as less severe, downplaying fear and emphasising positive developments. In contrast, both Caixin Weekly and Sanlian Lifeweek frequently reported on cases of recovered individuals testing positive again, with Caixin Weekly offering more in-depth discussions on the potential for survivors to remain contagious. While the negative impacts of COVID-19 on survivors’ labour and social capacities were not a major focus in most outlets, these impacts were still present, particularly in People’s Daily and Sanlian Lifeweek, which reported more significant negative effects on survivors’ social functions. Across both state-sponsored and market-oriented outlets, mixed messages emerged regarding the social acceptance of survivors, with articles simultaneously advocating for social distancing while promoting reintegration. These findings underscore the complexity of media portrayals, revealing a diverse reporting landscape characterised by mixed messages. Conclusion This study reveals the presence of conflicting media narratives, which have potentially contributed to the societal stigma surrounding COVID-19 survivors. The mixed messages—simultaneously promoting both fear and acceptance—have exacerbated public confusion and misconceptions. The findings underscore the critical need for clear, consistent, and evidence-based reporting during public health crises to mitigate stigma and enhance the public’s understanding of health-related information.